2012
DOI: 10.1017/s1751731111001947
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of terpenes and terpenoids from Mediterranean rangelands by mixed rumen bacteria in vitro

Abstract: This in vitro study aimed at estimating the disappearance rates of 14 terpenes and terpenoids after 24-h incubation with mixed bacteria from caprine rumens. These compounds comprised nine monoterpene hydrocarbons (d-3-carene, p-cymene, b-myrcene, (E)-and (Z)-b-ocimene, a-phellandrene, a-terpinene, g-terpinene and a-terpinolene), four oxygenated monoterpenes ((E)-and (Z)-linalool oxide, 4-terpinenol, a 1 g terpineol) and one sesquiterpene hydrocarbon (b-cedrene). They were individually exposed to goat rumen mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…M. teretifolia contains the highest neral and geranial concentrations of all Melaleucas, while a major secondary constituent in M. ericifolia is linalool, all known to have antimicrobial properties . It has also been reported that terpenoids remain undegraded in the rumen for a prolonged period, hence their activity is extended. However, all EO tested here also inhibited overall microbial activity, a similar finding having previously been reported, suggesting that inclusion of EOs in diets at these doses could compromise energy supply to ruminants.…”
Section: Discussionsupporting
confidence: 88%
“…M. teretifolia contains the highest neral and geranial concentrations of all Melaleucas, while a major secondary constituent in M. ericifolia is linalool, all known to have antimicrobial properties . It has also been reported that terpenoids remain undegraded in the rumen for a prolonged period, hence their activity is extended. However, all EO tested here also inhibited overall microbial activity, a similar finding having previously been reported, suggesting that inclusion of EOs in diets at these doses could compromise energy supply to ruminants.…”
Section: Discussionsupporting
confidence: 88%
“…Kim et al 2016). Furthermore, we know that numerous plant defence compounds, such as monoterpenes, diterpenes, phenolics and alkaloids can be metabolized by bacteria (Malecky et al 2012, Marmulla and Harder 2014, Hammer and Bowers 2015, Vilanova et al 2016, and crucially, some invasive insects seem able to tolerate (Piskorski et al 2011) and even benefit (Lefort et al 2015) from such compounds. The presence of gut microbial communities capable of metabolising plant defence compounds (Chung et al 2017) could explain why some phytophagous insects are invasive whilst others are not.…”
Section: Literature Supportmentioning
confidence: 99%
“…However, the ability to degrade and utilize terpenes is not limited to environmental microorganisms, but also occurs in symbiotic microbes associated with vertebrates and invertebrates. Goat rumen-associated bacteria can degrade several monoterpenes (Malecky, Albarello, & Broudiscou, 2012), and some members of the gut community of bark beetles are capable of in vitro degradation of monoterpenes and diterpenes (Boone et al, 2013;Xu, Lu, & Sun, 2015). However, whether bacterial degradation of terpenes occurs within the insects as well has not been explored.…”
Section: Introductionmentioning
confidence: 99%